PROFIL KEMAMPUAN BERPIKIR KREATIF SISWA SEKOLAH MENENGAH PERTAMA DITINJAU DARI TINGKAT KECEMASAN MATEMATIKA DAN JENDER - Wahyuningrum, Endang; Pratiwi, Disti; Adji, Sandra Sukmaning (Jurnal Pendidikan, 2019)
<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">The purpose of this study was to describe the creative thinking skills of junior high school students <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">based on<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;"> mathematics anxiety<span style="color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">and gender<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">. <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">Aspects<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;"> of creative thinking skills used in this study are fluency, flexibility, and novelty.<span style="color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">This research is a qualitative descriptive study<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">.<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;"> The instruments used were open-ended questions consisting of algebra and geometry questions, mathematics anxiety questionnaires, and interview guidelines. <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">The study was conducted in class IX E of SMPI Al Azhar 12 Rawamangun Jakarta.<span style="color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">The subject of this study consisted of four students<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">, they are<span style="color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">male student with low mathematics anxiety<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">, <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">female student with low mathematics anxiety<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">, <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">male student with medium mathematics anxiety<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">, and <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">female student with medium mathematics anxiety<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">.<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">The results of the mathematics anxiety questionnaire showed that none of the students in class IX E had high math anxiety<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">. T<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">here are differences in the fulfillment of aspects of creative <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">thinking in terms of differences in <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">mathematics <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">anxiety and gender levels<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">. S<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">tudents with low math anxiety fulfill aspects of fluency<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">, <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">flexibility<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">, and novelty<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;"> in algebra<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;"> and geometry<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;"> questions<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">. S<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">tudents with <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">medium<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;"> math anxiety fulfill aspects of fluency<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;"> and <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">flexibility<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;"> both <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">in algebra<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;"> and geometry<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;"> questions<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">. <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">Female students fulfill aspects of <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">fluency<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">, flexibility, and novelty both in algebra and geometry<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;"> questions<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">. <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">M<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">ale students<span style="color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">fulfill aspects of fluency and flexibility in algebra <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">questions, while in geometry questions the aspects that are fulfilled are <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">fluency<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">, <em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">flexibility<em style="box-sizing: border-box; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;">, and novelty.